Agro-Dealers and the Political Economy of Agricultural Biotechnology Policy in Kenya - Odame, Hannington; Muange, Elijah (Future Agricultures Consortium, 2011)
Public and private actors and their networks are committing substantial resources to support agro-dealers to deliver novel technologies and information in line with the New Green Revolution for Africa. The main point of entry has been the cereal seed system, with a focus on maize seed in particular, which is seen as both a key staple and a politically important crop. In Kenya, the seed system landscape has been changing dramatically in recent years, with the entry of highly influential seed companies, biotechnology research and legislation of the biosafety regulations. Thus, the prospect of genetically modified (GM) crops being pushed through agribusiness networks is an emerging issue, raising the question of whether small-scale, independent stockists or ‘agro-dealers’ have the capacity to deliver these technologies and provide local regulatory control over the new seeds. This study sought to investigate the policy and institutional environment within which agricultural biotechnology agro-dealers have evolved, as well as the agendas that are being pushed by particular interests in the new pro-GM policy and institutional environment in Kenya and their expected outcomes. In response to this evolving situation, an agro-dealer survey was conducted in high- and low-rainfall areas, in addition to an examination of two maize projects: STRIGAWAY® Technology and Water Efficient Maize for Africa (WEMA). STRIGAWAY® Technology is expected to provide a test case for delivering WEMA to smallholder farmers, with agro-dealership at the core of the initiative. Research conducted by this study has found that the current commercial model of agro-dealership is faced with several challenges, raising issues concerning its sustainability in delivering novel technologies. Agro-dealers lack adequate knowledge of the current commercial cereal seed varieties, and are also ill-equipped to address farmers’ concerns on the utilization of existing technologies. The feedback mechanisms to address farmers’ concerns are weak, and promises made to address these weaknesses remain unfulfilled. Agro-dealers operate on a small capital base which limits their ability to procure meaningful stocks for new technological products. New technological products are rife with demand risks for agro-dealers. Many dealers seek assurance that their investments in new technologies can stimulate sufficient farmer demand to secure positive returns. Agro-dealers have called for demand stimulation through guaranteed markets for agricultural outputs and the stabilisation of output prices. It is seen that this would then lead to increased demand for the new technologies. Regulatory enforcement has been a major constraint in the seed trade, leaving trading loopholes that have allowed ‘fake’ and poor quality seeds and unlicensed agro-dealers to infiltrate the system. Unless synergies are developed among agencies in charge of regulating agro-dealership, illegal agro-dealers and the proliferation of poor quality, adulterated and counterfeit inputs will continue to flourish, ruining the efforts of a New Green Revolution in Kenya delivered by agro-dealers. Farmers and agro-dealers welcome the potential benefits of GM crops and seed, but they are wary of the perceived concurrent risks. A specific risk that has been identified is the erosion of genetic diversity in the smallholder farming, a result of gene flow, which is believed will lead to the disappearance of traditional varieties and the reliance of farmers on expensive external inputs. The Kenyan agro-dealership in its present state is not capable of efficiently delivering GM seeds to farmers and providing a front-line regulatory service for their use. Extending trade in this new agricultural technology will require a much higher level of technical skills in agro-dealers than conventional technologies have demanded previously. Dealers will also be responding to new regulatory, economic and social challenges. Engaging Kenyan agro-dealers in GM technology delivery must take these governance issues into consideration if it is to be carried out successfully.